CARDIOTHORACIC RATIO IN SUNDA PORCUPINE (Hystrix javanica) - Suparmin, Yuliani; Noviana, Deni; Gunanti, Gunanti; Agungpriyono, Srihadi (Jurnal Kedokteran Hewan, 2023)
The present study aimed to standardize cardiothoracic ratio (CTR) in clinically healthy Sunda porcupine. This study was an explorative study using four Sunda porcupines, male and female, with an estimated age of 6 months-2years. The sampled animals were radiographed in ventrodorsally projection using a digital X-ray machine with 50 kVp and 6 mAs. Each animal was injected with xylazine as sedation agent at 2 mg/kg BW, intramuscularly route in the dorsal part of animals tail. The radiogram showed that Sunda porcupine heart tends to be round and more massive, characterized as the convex edge of the heart. The cardiothoracic ratio (CTR) showed that the ratio of the broadest expansion of the heart relative to the thoracic width in a ventrodorsally projection ranged from 0.48-0.55 with an average 0.52. Standard heart size was less than half of the largest thoracic diameter (normal CTR0.5). Sunda porcupine heart tends to be round and larger characterized as the convex edge of the heart. The CTR values obtained were 0.48-0.55.